2015
DOI: 10.1063/1.4916632
|View full text |Cite
|
Sign up to set email alerts
|

Movement of basal plane dislocations in GaN during electron beam irradiation

Abstract: The movement of basal plane segments of dislocations in low-dislocation-density GaN films grown by epitaxial lateral overgrowth as a result of irradiation with the probing beam of a scanning electron microscope was detected by means of electron beam induced current. Only a small fraction of the basal plane dislocations was susceptible to such changes and the movement was limited to relatively short distances. The effect is explained by the radiation enhanced dislocation glide for dislocations pinned by two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…This difference was similar for films with different average donor concentration, which allowed for a possible explanation of the effect. 157 Similar investigations of neutron irradiated films showed that this method can reveal inhomogeneous radiation defect accumulation.…”
Section: Movement Of Dislocations In Gan During Electron Beam Irradiamentioning
confidence: 82%
See 2 more Smart Citations
“…This difference was similar for films with different average donor concentration, which allowed for a possible explanation of the effect. 157 Similar investigations of neutron irradiated films showed that this method can reveal inhomogeneous radiation defect accumulation.…”
Section: Movement Of Dislocations In Gan During Electron Beam Irradiamentioning
confidence: 82%
“…Yakimov et al 157 demonstrated dislocation movement upon irradiation by the probing electron beam of a scanning electron microscope. The effect was registered only for the segments of dislocations lying in the basal plane.…”
Section: Movement Of Dislocations In Gan During Electron Beam Irradiamentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation damage in wide bandgap semiconductors is attracting increasing interest, especially in GaN. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Recently, it has become clear that β-Ga 2 O 3 is attractive for high temperature applications in harsh environments that cannot be tolerated by conventional electronics. [17][18][19][20][21][22][23][24][25][26][27][28][29] Its wide bandgap allows operation at elevated temperatures, while it is also radiation hard and may provide improved performance over GaN.…”
mentioning
confidence: 99%
“…. The underlying mechanism of such relaxation might be the irradiation‐enhanced point or extended defects redistribution, especially taking into account that the recombination‐enhanced dislocation glide in GaN has been already observed under e‐beam irradiation. A study of CL spectrum dependence on applied bias before and after LEEBI allowed to assume that a dissociation of Mg–H complexes in the upper p‐GaN layer and subsequent hydrogen diffusion into active layer can also be involved in the modification of InGaN MQW optical properties .…”
Section: Introductionmentioning
confidence: 99%